A portable X-ray diffraction apparatus for in situ analyses of masters’ paintings - Eveno, Myriam; Duran, Adrian; Castaing, Jacques (Applied physics. A, Materials science & processing, 2010)
It is rare that the analyses of materials in paintings can be carried out by taking micro-samples. Valuable works of art are best studied in situ by non-invasive techniques. For that purpose, a portable X-ray diffraction and fluorescence apparatus has been designed and constructed at the C2RMF. This apparatus has been used for paintings of Rembrandt, Leonardo da Vinci, Van Gogh, Mantegna, etc. Results are given to illustrate the performance of X-ray diffraction, especially when X-ray fluorescence does not bring sufficient information to conclude.